Feasibility and perceived utility of immersive virtual reality for training radiology residents in contrast reaction management: a pilot study - Karp, John D.; Weber, Daniel; Sheng, Mike; Harrison, Neil E.; Gade, Terence P.; Williams, Noel; Dumon, Kristoffel; Dhanaliwala, Ali H. (Frontiers in Virtual Reality, 2025)
PurposeMillions of contrast-enhanced CTs are performed every year, resulting in thousands of contrast reactions that require prompt assessment. Radiologists tasked with responding to these patients must develop and maintain appropriate skills, which can be difficult in the absence of consistent exposure or practice. The aim of this study was to evaluate the efficacy of virtual reality (VR) for teaching radiology residents how to manage contrast reactions.ApproachA custom VR application was developed to simulate contrast reaction scenarios. First-year radiology residents were asked to complete the VR simulation in parallel with an in-person, instructor-led workshop. After completing the VR simulation, an anonymous survey was used to assess views towards and experience of the simulator via components of previously validated instruments including motion sickness, realism, task load, and technology access and awareness.ResultsA total of 11 participants completed the VR contrast reaction simulation and survey. Post-simulation survey results found that 91% thought VR could be useful for radiology education, 82% reported an intent to use the technology again in the future, and 73% thought the VR simulation would be useful for maintaining their skills. 54% reported some level of general discomfort and 18% reported severe headache. A Fisher exact test found no correlation between perceived usefulness and discomfort (p = 1).ConclusionInitial findings of this pilot study suggest radiology residents are open to utilizing VR tools, despite moderate levels of discomfort, but view these tools as education adjuncts. However, given the small sample size, continued investigation is needed to better understand the role of VR for primary education versus maintenance of skills.